Anticonvulsant activity of Bacopa monniera in rodents - Darpan Kaushik; Ashish Tripathi; Rashmi Tripathi; Madiwalayya Ganachari; Suroor Ahmad Khan (Universidade de São Paulo, 2009)
Bacopa monnieri (L), belonging to the Scrophulariaceae family and commonly known as Brahmi, is well known in India for its CNS activity but its neuropharmacological effect has not yet been explored. In the present study, the antiepileptic effects of the plant were investigated. The ethanolic extract of Bacopa monniera was tested for anticonvulsant activity in albino rats, using different convulsive models. The ethanolic extract of leaves produced significant anticonvulsant activity for all the different models studied. The present study shows a probable mechanism of action similar to that of benzodiazepines (GABA agonist). Thus, these results emphasize the need to diversify by using alternative therapeutic approaches pertaining to herbal medicine, where a single easily available plant may provide solutions to several therapeutic challenges, as observed in the anticonvulsant action of ethanolic extract of B. monniera. Bacopa monniera, da família Scrophulariaceae, e comumente denominada Brahmi, é bem conhecida na Índia por sua atividade no Sistema Nervoso Central, mas seu efeito neurofarmacológico não foi, ainda, explorado. No presente estudo, investigaram-se os efeitos antiepilépticos da planta. O extrato etanólico da Bacopa monniera foi testado quanto à atividade anticonvulsivante em ratos albinos, utilizando-se diferentes modelos de convulsão. O extrato etanólico das folhas produziu atividade anticonvulsivante significativa para todos os diferentes modelos estudados. O presente estudo mostra provável mecanismo de ação semelhante ao dos benzodiazepínicos (agonista do GABA). Assim sendo, esses resultados enfatizam a necessidade de diversificar, utilizando-se abordagens terapêuticas alternativas da medicina natural, em que uma planta facilmente disponível pode fornecer soluções para vários desafios terapêuticos, como o observado na ação anticonvulsivante do extrato etanólico de Bacopa monniera.